Dopaminergic Regulation of Circadian Food Anticipatory Activity Rhythms in the Rat - Smit, Andrea N. (Public Library of Science, 2013)
Circadian activity rhythms are jointly controlled by a master pacemaker in the hypothalamic suprachiasmatic nuclei (SCN) and by food-entrainable circadian oscillators (FEOs) located elsewhere. The SCN mediates synchrony to daily light-dark cycles, whereas FEOs generate activity rhythms synchronized with regular daily mealtimes. The location of FEOs generating food anticipation rhythms, and the pathways that entrain these FEOs, remain to be clarified. To gain insight into entrainment pathways, we developed a protocol for measuring phase shifts of anticipatory activity rhythms in response to pharmacological probes. We used this protocol to examine a role for dopamine signaling in the timing of circadian food anticipation. To generate a stable food anticipation rhythm, rats were fed 3h/day beginning 6-h after lights-on or in constant light for at least 3 weeks. Rats then received the D2 agonist quinpirole (1 mg/kg IP) alone or after pretreatment with the dopamine synthesis inhibitor α-methylparatyrosine (AMPT). By comparison with vehicle injections, quinpirole administered 1-h before lights-off (19h before mealtime) induced a phase delay of activity onset prior to the next meal. Delay shifts were larger in rats pretreated with AMPT, and smaller following quinpirole administered 4-h after lights-on. A significant shift was not observed in response to the D1 agonist SKF81297. These results provide evidence that signaling at D2 receptors is involved in phase control of FEOs responsible for circadian food anticipatory rhythms in rats.